Quality of life in patients with advanced ovarian cancer under personalised treatment: the impact of HIPEC - V. Maksymovskyi; A. Rybin; V. Zamyshlyak (Journal of Education, Health and Sport)
Ovarian cancer ranks first among gynaecological cancers in terms of mortality, mainly due to late detection and high recurrence rates. The standard treatment for late stages remains cytoreductive surgery combined with systemic chemotherapy. However, survival and quality of life for patients receiving traditional treatment remain unsatisfactory. The aim of the study was to analyse the quality of life of patients with primary advanced ovarian cancer depending on the type of personalised management before the start of specialised treatment, after cytoreductive surgery in the early and late postoperative periods, during chemotherapy and after the end of specialised treatment.